An evaluation of an agroforestry system with 2-year-old sengon (Paraserianthes falcataria) and shade-tolerant upland rice - SAHIDA HAURANI TSANIYA; NURHENI WIJAYANTO; DESTA WIRNAS (Society for Indonesian Biodiversity, 2022)
Abstract. Tsaniya SH, Wijayanto N, Wirnas D. 2022. An evaluation of an agroforestry system with 2-year-old sengon (Paraserianthes falcataria) and shade-tolerant upland rice. Biodiversitas 23: 1159-1166. Sengon is tree species that is often cultivated with upland rice in agroforestry systems. The main obstacle of rice development in agroforestry systems are competition between plants for sunlight and nutrients. 2-year-old sengon has a wider canopy and longer roots, increasing competition between sengon and rice. Planting upland rice in this condition requires strategies, such as selecting shade-tolerant rice varieties and rice plantations inside bamboo. This study aimed to evaluate the agroforestry system of sengon and shade-tolerant upland rice when the sengon plants were two years old and evaluate the effectiveness of using bamboo to reduce the competition between sengon and upland rice. This research was conducted from November 2020 to April 2021 in the Cikabayan Forest, IPB University, Bogor, West Java. This study one-factor completely randomized design to analyze the growth of sengon provenances and a three-factor completely randomized design with three replications to analyze the growth and yield of rice. The first factor was the cultivation system (Solomon F1 agroforestry, Solomon F2 agroforestry, local sengon agroforestry, and rice monoculture), the second factor was the planting method (using bamboo and without bamboo), and the third factor was rice varieties (Rindang 1 Agritan and Rindang 2 Agritan). The results showed that Solomon and local sengon in this study had a growth that was not significantly different and had low diversity. The results also showed that 2-year-old sengon spacing 3 m x 1.5 m caused great shade and high competition, leading to low rice yields.